Islamic Inheritance Law (Faraid) and Its Economic Implication - Adelina Zuleika; Ni Putu Desinthya (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective - This paper attempts to discuss the Islamic law of inheritance (Faraid), its existence and its systematic impact to humankind. Faraid plays a fundamental role as an impetus behind the development of science, which has a great economic impact to the development of social welfare. This paper aims to increase the awareness towards the importance of Islamic law of Inheritance for knowledge development, and social prosperity of humankind. Secondly, to reveal the hikmah behind the rules set in Faraid and their economic implications. Thirdly is to emerge the consciousness for being Sharia’ compliance by revealing the secret behind His rules and its benefit for humankind.Method - Employing a qualitative method and literature reviewResult - This paper shows that from the macroeconomic perspective, Faraid systematically ensures the redistribution of wealth, and spreads the concentration of wealth in every generation. Literature reviews and information collected are employed in order to analyze and make further inferences. The literature review clarifies the magnificence of Faraid and its real contribution to human development; in economics and in other disciplines. Faraid keeps the justice in wealth distribution, protects property rights, empowers women to be involved in economic activities and as a whole, Faraid also encourages economic growth.Conclusion - Conclusively, by commissioning Faraid, the wealth is generated and returned to the factors production through many hands of who deserve it after the absence of deceased.Keywords : Islamic Inheritance Law; Faraid; Property Rights; Distribution of Wealth